Characteristics and quality of systematic reviews and meta-analyses of observational nutritional epidemiology: a cross-sectional study. Issue 6 (19th March 2021) - Zeraatkar, Dena; Bhasin, Arrti; Morassut, Rita E; Churchill, Isabella; Gupta, Arnav; Lawson, Daeria O; Miroshnychenko, Anna; Sirotich, Emily; Aryal, Komal; Mikhail, David; Khan, Tauseef A; Ha, Vanessa; et al.
ABSTRACT: Background: Dietary recommendations and policies should be guided by rigorous systematic reviews. Reviews that are of poor methodological quality may be ineffective or misleading. Most of the evidence in nutrition comes from nonrandomized studies of nutritional exposures (usually referred to as nutritional epidemiology studies), but to date methodological evaluations of the quality of systematic reviews of such studies have been sparse and inconsistent. Objectives: We aimed to investigate the quality of recently published systematic reviews and meta-analyses of nutritional epidemiology studies and to propose guidance addressing major limitations. Methods: We searched MEDLINE (January 2018–August 2019), EMBASE (January 2018–August 2019), and the Cochrane Database of Systematic Reviews (January 2018–February 2019) for systematic reviews of nutritional epidemiology studies. We included a random sample of 150 reviews. Results: Most reviews were published by authors from Asia ( n = 49; 32.7%) or Europe ( n = 43; 28.7%) and investigated foods or beverages ( n = 60; 40.0%) and cancer morbidity and mortality ( n = 54; 36%). Reviews often had important limitations: less than one-quarter ( n = 30; 20.0%) reported preregistration of a protocol and almost one-third ( n = 42; 28.0%) did not report a replicable search strategy. Suboptimal practices and errors in the synthesis of results were common: one-quarter of meta-analyses ( n = 30; 26.1%) selected the meta-analytic model based on statistical indicators of heterogeneity and almost half of meta-analyses ( n = 50; 43.5%) did not consider dose–response associations even when it was appropriate to do so. Only 16 (10.7%) reviews used an established system to evaluate the certainty of evidence. Conclusions: Systematic reviews of nutritional epidemiology studies often have serious limitations. Authors can improve future reviews by involving statisticians, methodologists, and researchers with substantive knowledge in the specific area of nutrition being studied and using a rigorous and transparent system to evaluate the certainty of evidence.